Economic Crises and Institutions for Regional Economic Cooperation - C. Randall Henning (Asian Development Bank (ADB), 2011)
This paper examines the extent to which economic crises facilitate the development of more effective regional institutions and whether such institutions can shield regions from crises. It compares six regional economic crises over the last four decades and the institution building—or decay—that followed. The analysis concludes that five conditions are especially important in generating a constructive regional response: (i) a significant degree of regional economic interdependence; (ii) an independent secretariat or intergovernmental body charged with cooperation; (iii) webs of interlocking economic agreements; and, as elements of the multilateral context, (iv) conflict with the relevant international organization (such as the International Monetary Fund [IMF]); and (v) the support of the United States. The paper then reviews three episodes of crises in Europe, concluding that the Economic and Monetary Union (EMU) has deflected balance of payments and currency crises but not crises of other types, such as sovereign debt crises. Asian regionalism would be well served by heads of government taking the lead and delegating tasks to intergovernmental networks and secretariats, central banks and finance ministries retaining substantial collective autonomy in their fields of responsibility, and the use of concentric circles to accommodate countries with different levels of commitment to regionalism.
hdl:11540/2024
Keywords: F33; F36; F55; F59; 330; Economic crises; financial crises; regional institutions; Asian regionalism; regional integration